Influence of neuromuscular training interventions on jump-landing biomechanics and implications for ACL injuries in youth females: a systematic review and meta-analysis - Ramachandran, A. K.; Pedley, J. S.; Moeskops, S.; Oliver, J. L.; Myer, G. D.; Hsiao, H.-I.; Lloyd, R. S. (Sports Medicine, 2025)
Background: Various exercise interventions are recommended to reduce the risk of anterior cruciate ligament (ACL) injury in females. However, the extent to which these training interventions influence lower-limb landing biomechanics in youth female remains unclear. Objective: This systematic review and meta-analysis aimed to quantitatively summarise the effectiveness of various training interventions on jump-landing biomechanics in youth females. Methods: We systematically searched PubMed, SPORTDiscus, EMBASE and Scopus. Articles were included if they: (1) conducted research on uninjured youth females (reported mean age < 18 years) with no restriction on playing level/experience or physical activity level; (2) performed any form of training intervention for = 4 weeks; (3) reported any lower-limb kinematic (flexion/extension, adduction/abduction or internal/external rotation angles) or kinetic (joint moments or vertical ground reaction forces) data during the landing phase of jump-landing tasks, pre- and post-training intervention for both experimental and control groups, using a two- or three-dimensional motion capture system; (4) were randomised- or non-randomised controlled trials. The quality of the randomised controlled trials was assessed using the Risk of Bias tool 2, whereas the Downs and Black checklist was used for assessing the quality of non-randomised controlled trials. A multi-level meta-analytical model was used for conducting the quantitative analysis. Results: Thirteen studies (7 randomised controlled, 6 non-randomised controlled studies) involving 648 female participants were included in the final analyses. With regards to the overall quality of the included studies, three studies had high risk of bias while ten studies had some concerns. As part of the meta-analysis, we were able to analyse seven kinematic variables and two kinetic variables in aggregate. Compared with controls, the experimental group had significantly increased peak knee flexion angle (g = 0.58, p = 0.05) and reduced knee valgus motion (g = - 0.86, p = 0.05) post-intervention. The effects on other kinematic and kinetic variables ranged from trivial to moderate and were not significantly altered as a result of various training interventions. Conclusion: The findings from the synthesised literature indicate that training interventions have small to moderate effects on peak knee flexion angle and knee valgus motion during jumping tasks. However, further research employing more consistent study designs and methodologies is required to better understand the changes in jump-landing biomechanics in the youth female population following training interventions.